IMPACTO AMBIENTAL GENERADO POR LAS ACTIVIDADES QUÍMICAS DE PRODUCCIÓN Y USO DE CLOROFLUOROCARBONOS - Guerrero Santafé, Jaime Enrique (Tecné, Episteme y Didaxis: TED, 2000)
The purpose of the present publication is to discuss and analyzed the transcendence and magnitude of the impact produced by chemical activities over the environment, using a specific problem, the reduction of stratospheric ozone layer caused by the use of chlorofluorocarbons